Epidemiology and Economic Burden of an Outbreak of Cyclopeptide-Containing Mushroom Poisoning in the West of Iran - Karami Matin, Behzad; Amrollahi-Sharifabadi, Mohammad; Rezaei, Satar; Heidari, Afshar; Kazemi-Karyani, Ali (Frontiers in Public Health, 2022)
Little evidence is available on the epidemiological and economical dimensions of certain foodborne diseases such as wild mushroom poisoning. This study aimed to investigate the epidemiology and estimate the costs of poisoning with cyclopeptide-containing mushrooms in Kermanshah province in 2018. In this study, poisoning was investigated in different subgroups. The cost of illness method with a bottom-up approach was used to estimate the poisoning costs. Both direct and indirect costs of the poisoning were included in the analysis. The perspective of the study was society. Required data were obtained from the medical records of Imam Khomeini hospital and completed through a line survey with the patients. Two hundred eighty-three patients were poisoned in Kermanshah due to poisoning with cyclopeptide-containing mushrooms. Of 283 patients, 143 (50.53%) were men and 59.01% of patients were rural residents. About 43% of admissions were out-patient cases and 40% of patients were hospitalized within 1–3 days. Also, eight patients were pronounced dead in the area. The total cost of poisoning with cyclopeptide-containing mushrooms in Kermanshah province was 1,259,349.26. Of that, 69,281.65 was related to direct medical costs and 10,727.23 was direct non-medical costs. The indirect costs of death were estimated to be 1,125,829.7. The current study revealed that there is a significant financial burden due to cyclopeptide-containing mushrooms on patients, the health system, and society as a whole. Further studies are recommended to clarify the epidemiological and economic burden of foodborne illnesses related to wild mushroom poisonings. Sharing the outputs with health authorities, and informing the general public are warranted to reduce the burden of such diseases.